A process evaluation of user fees abolition for pregnant women and children under five years in two districts in Niger (West Africa) - Ridde Valéry; Diarra Aissa (BMC, 2009)
Abstract Background African policy-makers are increasingly considering abolishing user fees as a solution to improve access to health care systems. There is little evidence on this subject in West Africa, and particularly in countries that have organized their healthcare system on the basis of the Bamako Initiative. This article presents a process evaluation of an NGO intervention to abolish user fees in Niger for children under five years and pregnant women. Methods The intervention was launched in 2006 in two health districts and 43 health centres. The intervention consisted of abolishing user fees and improving the quality of services (drugs, ambulance, etc.). We carried out a process evaluation in April 2007 using qualitative and quantitative data. Three data collection methods were used: i) individual in-depth interviews (n = 85) and focus groups (n = 8); ii) participant observation in 12 health centres; and iii) self-administered structured questionnaires (n = 51 health staff). Results The population favoured abolition; health officials and local decision-makers were in favour, but they worried about its sustainability. Among health workers, opposition to providing free services was more widespread. The strengths of the process were: a top-down phase of information and raising community awareness; appropriate incentive measures; a good drug supply system; and the organization of a medical evacuation system. The major weaknesses of the process were: the perverse effects of incentive bonuses; the lack of community-based management committees' involvement in the management; the creation of a system running in parallel with the BI system; the lack of action to support the service offer; and the poor coordination of the availability of free services at different levels of the health pyramid. Some unintended outcomes are also documented. Conclusion The linkages between systems in which some patients pay (Bamako Initiative) and some do not should be carefully considered and organized in accordance with the local reality. For the poorest patients to really benefit, it is essential that, at the same time, the quality of services be improved and mechanisms be put in place to prevent abuses. Much remains to be done to generate knowledge on the processes for abolishing fees in West Africa.